2014
DOI: 10.1590/0104-6632.20140313s00002506
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physicochemical characterization of titanium oxide and sulfated titanium oxide obtained by thermal hydrolysis of titanium tetrachloride

Abstract: -This work reports the synthesis of titanium oxide (TiO 2 ) and sulfated titanium oxide (TiO 2 -SO 4 2-) obtained by thermal hydrolysis of titanium tetrachloride. Titanium hydroxide synthesized by this method was impregnated with a 1 N H 2 SO 4 solution, to give amounts of sulfate ions (SO 4 2-) of 3 and 7 wt%. The synthesized samples were dried at 120 °C during 24 h and then calcined for 3 h at 400 °C. Thermal analyses, X-ray diffraction, nitrogen physisorption, infrared spectroscopy, potentiometric titration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Temvuttirojn et al used XRD to analyze the synthesized SO 4 2– /ZrO 2 and found that the peak intensity would decrease after impregnation with sulfuric acid because the surface of ZrO 2 was anchored by SO 4 2– . There are also other studies demonstrating that the sulfation treatment can inhibit the crystallization of metal oxides, thereby weakening the peak intensity of its XRD diffraction peaks …”
Section: Resultsmentioning
confidence: 99%
“…Temvuttirojn et al used XRD to analyze the synthesized SO 4 2– /ZrO 2 and found that the peak intensity would decrease after impregnation with sulfuric acid because the surface of ZrO 2 was anchored by SO 4 2– . There are also other studies demonstrating that the sulfation treatment can inhibit the crystallization of metal oxides, thereby weakening the peak intensity of its XRD diffraction peaks …”
Section: Resultsmentioning
confidence: 99%
“…In HCP25, possible C-H bending is covered by Ti-O stretching [33,44,53]. A feature around 1450 cm −1 can be attributed to the C-O carboxyl group, which is especially visible for HCP25 [54]. The peak at 1620 cm −1 for both the materials is related to the skeletal vibration of the unoxidized graphitic domains.…”
Section: Characterizationmentioning
confidence: 92%
“…The FTIR spectra of TiO 2 -based doping agents and TiO 2 are compared in Figure 2. TiO 2 bands located at 715 and 1026 cm −1 are attributed to Ti-O bonds, and the bands at 3387, 1622 and 1396 cm −1 correspond to O-H bonds due to the moisture sorption on the powder surface [23]. In the case of SO 4 -TiO 2 , a strong band at 1153 cm −1 is attributed to sulfate ion coordinated to the Ti 4+ metal cation.…”
Section: Characterization Of Po 4 -Tio 2 and So 4 -Tio 2 Doping Agentsmentioning
confidence: 99%
“…The functionalization of TiO 2 either with the PO 4 3− anion or SO 4 2− anion was done by an impregnation-calcination method according to the literature [22][23][24] and is explained briefly herein. The PO 4 -TiO 2 powder was obtained as follows: TiO 2 powder was mixed with 0.1 M H 3 PO 4 in a 1:1 molar ratio and the solution was shaken in a water bath (80 • C).…”
Section: Synthesis Of Po 4 -Tio 2 and So 4 -Tio 2 Nanotubes Doping Agmentioning
confidence: 99%